My heart is a chainsaw - Jones, Stephen Graham, 1972- (New York : Saga Press, 2021)
"Jade Daniels is an half-Indian outcast with an abusive father, an absent mother, and an entire town that wants nothing to do with her. Jade watches horror movies, especially the ones where a masked killer seeks revenge on a world that wronged them, for comfort. And Jade narrates the quirky history of Proofrock as if it is one of those movies. But when blood actually starts to spill into the waters of Indian Lake, she pulls us into her dizzying, encyclopedic mind of blood and masked murderers, and predicts exactly how the plot will unfold." --
Keywords: Horror films -- Fiction; Abandoned children -- Fiction; Abused children -- Fiction; Dysfunctional families -- Fiction; Psychic trauma -- Fiction; Teenage girls -- Fiction; Indigenous peoples -- Idaho -- Fiction; Horror fiction; Thrillers (fiction).